Misi Kristiani di Tengah Pluralitas: Dialog Iman sebagai Wujud Kesaksian Injil - Miracle Mendeh; Ramli Sarimbangun; Irfandy Kentey; Ekaputra Merentek; Anastasia Dumondor (PT. Giat Konseling Nusantara, 2026)
This article examines the mission of the church within the context of religious and cultural pluralism in Indonesia by emphasizing interfaith dialogue as a relevant and contextual form of Christian witness. In a plural society vulnerable to identity-based conflicts and intolerance, the church is called to engage in mission not through exclusive or confrontational approaches, but through dialogical practices that respect human dignity and religious diversity. Grounded in the paradigm of Missio Dei, this study affirms that mission is the church’s participation in God’s ongoing work of love, justice, and reconciliation in the world. Through theological and biblical reflection, interfaith dialogue is understood not as syncretism or theological compromise, but as a faithful and incarnational expression of gospel witness. The article demonstrates that interfaith dialogue has strong biblical foundations and offers significant implications for contemporary churches, particularly in fostering interreligious relationships, social engagement, and transformative presence within Indonesia’s plural society.